TISIDB: an integrated repository portal for tumor–immune system interactions - Ru, Beibei; Wong, Ching Ngar; Tong, Yin; Zhong, Jia Yi; Zhong, Sophia Shek Wa; Wu, Wai Chung; Chu, Ka Chi; Wong, Choi Yiu; Lau, Chit Ying; Chen, Ian; Chan, Nam Wai; Zhang, Jiangwen (Bioinformatics, 2019)
Abstract Summary The interaction between tumor and immune system plays a crucial role in both cancer development and treatment response. To facilitate comprehensive investigation of tumor–immune interactions, we have designed a user-friendly web portal TISIDB, which integrated multiple types of data resources in oncoimmunology. First, we manually curated 4176 records from 2530 publications, which reported 988 genes related to anti-tumor immunity. Second, genes associated with the resistance or sensitivity of tumor cells to T cell-mediated killing and immunotherapy were identified by analyzing high-throughput screening and genomic profiling data. Third, associations between any gene and immune features, such as lymphocytes, immunomodulators and chemokines, were pre-calculated for 30 TCGA cancer types. In TISIDB, biologists can cross-check a gene of interest about its role in tumor–immune interactions through literature mining and high-throughput data analysis, and generate testable hypotheses and high quality figures for publication. Availability and implementation http://cis.hku.hk/TISIDB Supplementary information Supplementary data are available at Bioinformatics online.